Investigation of excited state, reductive quenching, and intramolecular electron transfer of Ru(ii)–Re(i) supramolecular photocatalysts for CO2 reduction using time-resolved IR measurements. Issue 11 (22nd February 2018) - Koike, Kazuhide; Grills, David C.; Tamaki, Yusuke; Fujita, Etsuko; Okubo, Kei; Yamazaki, Yasuomi; Saigo, Masaki; Mukuta, Tatsuhiko; Onda, Ken; Ishitani, Osamu
Abstract : Time-resolved IR spectra indicated fast electron transfer from the reduced photosensitizer to the catalyst. Abstract : Supramolecular photocatalysts in which Ru(ii ) photosensitizer and Re(i ) catalyst units are connected to each other by an ethylene linker are among the best known, most effective and durable photocatalytic systems for CO2 reduction. In this paper we report, for the first time, time-resolved infrared (TRIR) spectra of three of these binuclear complexes to uncover why the catalysts function so efficiently. Selective excitation of the Ru unit with a 532 nm laser pulse induces slow intramolecular electron transfer from the 3 MLCT excited state of the Ru unit to the Re unit, with rate constants of (1.0–1.1) × 10 4 s −1 as a major component and (3.5–4.3) × 10 6 s −1 as a minor component, in acetonitrile. The produced charge-separated state has a long lifetime, with charge recombination rate constants of only (6.5–8.4) × 10 4 s −1 . Thus, although it has a large driving force (−Δ G 0CR ∼ 2.6 eV), this process is in the Marcus inverted region. On the other hand, in the presence of 1-benzyl-1, 4-dihydronicotinamide (BNAH), reductive quenching of the excited Ru unit proceeds much faster ( k q [BNAH (0.2 M)] = (3.5–3.8) × 10 6 s −1 ) than the abovementioned intramolecular oxidative quenching, producing the one-electron-reduced species (OERS) of the Ru unit. Nanosecond TRIR data clearly show that intramolecular electron transfer from the OERS of the Ru unit to the Re unit ( k ET > 2 × 10 7 s −1 ) is much faster than from the excited state of the Ru unit, and that it is also faster than the reductive quenching process of the excited Ru unit by BNAH. To measure the exact value of k ET, picosecond TRIR spectroscopy and a stronger reductant were used. Thus, in the case of the binuclear complex with tri( p- fluorophenyl)phosphine ligands (RuRe(FPh) ), for which intramolecular electron transfer is expected to be the fastest among the three binuclear complexes, in the presence of 1, 3-dimethyl-2-phenyl-2, 3-dihydro-1 H -benzo[ d ]imidazole (BIH), k ET was measured as k ET = (1.4 ± 0.1) × 10 9 s −1 . This clearly shows that intramolecular electron transfer in these RuRe binuclear supramolecular photocatalysts is not the rate-determining process in the photocatalytic reduction of CO2, which is one of the main reasons why they work so efficiently.